Maternal and perinatal outcome in pregnancy induced hypertension and preeclampsia - Pairu, Jagannath; KN, Bharathi; George, Kristine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Presence of proteinuria in hypertensive disorders of pregnancy has profound effect on maternal and perinatal outcome. Pregnancy induced hypertension is characterized by hypertension and absence of proteinuria. Preeclampsia is characterized by hypertension and proteinuria. Methods: This is a hospital based prospective comparative study of maternal and perinatal outcome in pregnancy induced hypertension and preeclampsia. Results: Maternal complications were significant more in preeclampsia group compared to pregnancy induced hypertension group. Preterm deliveries, foetal growth restriction and still birth were more common in preeclampsia group. The rate of vaginal deliveries was more frequent in the group with pregnancy induced hypertension than preeclampsia. Conclusions: Presence of proteinuria is a predictor for poor maternal and perinatal outcome in hypertensive disorders of pregnancy.